Analisis Keterampilan Berpikir Tingkat Tinggi Siswa dalam Pemecahan Masalah Matematika Berdasarkan Taksonomi Anderson - Abdul Rahman; Asdar; Nur Indah Surahman (Program of Mathematics Education Department of Mathematics Faculty of Mathematics and Natural Sciences (FMIPA) Universitas Negeri Makassar (UNM), 2019)
This study is a qualitative study that aims to investigate description of analysis results the students’ higher order thinking skill in mathematics problem solving based on Anderson taxonomy. The descriptions were obtained by analysis the test results of students' higher order thinking skill in mathematics problem solving. The description is also supported by interview data after the test was conducted. Data validation technique using time triangulation is by conducting interviews to find the suitability of data sourced from the same problem at different times. Data analysis technique using data analysis steps according to Miles and Hubberman. This study conducted in SMAN 1 Mamuju with the number of subjects are 2 people that selected using by purposive sampling technique. The results of the study indicate that: (1)students’ higher order thinking skills who follow guidance of OSN Mathematics in mathematics problem solving based on Anderson’s taxonomy in analyzing category(C4) involving skills in understanding(C2) and applying(C3); evaluate category(C5) involving skills in understanding(C2), applying(C3) and analyzing(C4); while the creating category(C5) involving skill in analyzing (C4), (2) students’ higher order thinking of students who don’t follow guidance of OSN Mathematics in mathematics problem solving towards on Anderson's taxonomy in analyzing category(C4), that is not able to analyzing well because not able to understanding(C2) so mistaken in interpretation(C3); evaluating category(C5) involving skills in understanding(C2) and analyzing(C4); while creating category can’t be identified.